2020
DOI: 10.1093/conphys/coaa117
|View full text |Cite
|
Sign up to set email alerts
|

Negligible hormonal response following dehorning in free-ranging white rhinoceros (Ceratotherium simum)

Abstract: The white rhinoceros (Ceratotherium simum) is experiencing unsustainable poaching losses fuelled by a demand for horn. Increasingly, private and state reserves are dehorning their rhinoceros populations in an attempt to reduce poaching pressure. Rhinoceroses use their horns in social interactions as well as during resource access and so its partial removal as part of reserve management practices may adversely influence these behaviours. Physiological stress can correlate with animal welfare, reproductive state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…However, it is recommended that rhino are monitored if there are multiple consecutive high-visitor days to ensure that increased vigilance behavior are not associated with physiological effects such as elevated stress hormones. Such responses have been observed previously for rhino in stressful situations in the wild (Penny et al, 2020) and for other pachyderms in captivity (Grand et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…However, it is recommended that rhino are monitored if there are multiple consecutive high-visitor days to ensure that increased vigilance behavior are not associated with physiological effects such as elevated stress hormones. Such responses have been observed previously for rhino in stressful situations in the wild (Penny et al, 2020) and for other pachyderms in captivity (Grand et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Dehorning may also have an indirect stress effect through disturbance caused by the interventions required for dehorning, including vehicles, helicopters, and capture teams. The potential effects of dehorning have been investigated, with studies reporting its impact on a range of factors including calf survival (Berger and Cunningham 1994;Atkinson 1996;Du Toit and Anderson 2013), inter-calving interval (ICI) (Alibhai et al 2001;Atkinson et al 2002;Du Toit 2001;Penny et al 2020a), and corticosteroid levels (Badenhorst et al 2016;Penny et al 2020b). Dehorning was found to have no significant long-term effect on corticosteroid levels in two studies on white rhinos (Badenhorst et al 2016;Penny et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, du Toit and Anderson, (2013) reported that the dehorning of black rhinos did not affect the spatial locations of monitored individuals, finding no evidence of increased displacement. Recent research into the effects of dehorning in white rhinos found no evidence that the procedure influenced the duration of intercalf intervals or caused a long-term physiological stress response (Penny et al, 2020a(Penny et al, , 2020b. However, findings by Kretzschmar et al (2020) on the indicators of reproductive success in horned white rhinos was contradictory, identifying a strong positive correlation between horn size and the number of calves sired in one group of males but a negative correlation within another.…”
Section: Introductionmentioning
confidence: 99%